The immunosuppressive effects of bilirubin - Vĕtvicka, V; Síma, P; Miler, I; Bilej, M (Folia microbiologica, 1991)
The strong effects of bilirubin on various levels of the immune system are multifactorial. Concerning the mechanisms of these effects, we hypothesize that the primary causes of the described actions of bilirubin are the direct interaction of bilirubin molecules with cell membranes.
Keywords: bilirubin; Immunosuppressive Agents; Humans; imunosupresiva; Bilirubin; lidé